Berantas Hipertensi dengan Cerdik dan Patuh di RW 013 Kelurahan Kapuk Kecamatan Cengkareng - Solehudin Solehudin; Irma Herliana; Inas Syabanasyah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Hypertension is a major public health problem with an increasing prevalence and is often undetected due to its asymptomatic nature, leading to serious complications if not properly controlled. Low levels of public knowledge and poor adherence to preventive behaviors, routine health checks, and treatment remain significant challenges in hypertension management at the community level. This community service program aimed to improve public knowledge and awareness of hypertension through the implementation of the CERDIK and PATUH approaches. The program employed a community-based promotive and preventive method, including health education, blood pressure screening, and interactive discussion and counseling. The activity was conducted in RW 013, Kapuk Subdistrict, Cengkareng District, involving 60 adult and elderly participants. Knowledge levels were assessed using pre-test and post-test questionnaires and analyzed descriptively. The results demonstrated a substantial improvement in participants’ knowledge after the health education intervention, with the mean knowledge score increasing from 35 before the intervention to 80 after the intervention. In addition, the variation in knowledge levels among participants became more homogeneous following the educational activities. High community enthusiasm and active participation during the program reflected positive acceptance and engagement with the hypertension education initiative. This community service activity confirms that community-based health education using the CERDIK and PATUH approaches is effective as a promotive and preventive strategy to enhance public knowledge of hypertension. Improved knowledge is expected to encourage healthier lifestyle behaviors and greater adherence to hypertension control practices, thereby supporting sustainable and independent blood pressure management within the community.